2021
DOI: 10.3390/su13020983
|View full text |Cite
|
Sign up to set email alerts
|

Building Retrofit and Energy Conservation/Efficiency Review: A Techno-Environ-Economic Assessment of Heat Pump System Retrofit in Housing Stock

Abstract: The world has not been able to achieve minimum greenhouse gas emissions in buildings’ energy consumptions because the energy and emissions optimization techniques have not been fully utilized. Thermal comfort is one of the most important issues for both residential and commercial buildings. Out of the 40% of global energy consumed by buildings, a large fraction is used to maintain their thermal comfort. In this study, a comprehensive review of the recent advancements in building energy conservation and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 70 publications
0
8
0
1
Order By: Relevance
“…This understanding of NPV is used in capital budgeting and investment planning, enabling analysis of a projected investment or project [11]. The application of NPV in capital budgeting and investments is widely presented in the literature, e.g., [7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The researchers emphasise the importance of NPV for investment planning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This understanding of NPV is used in capital budgeting and investment planning, enabling analysis of a projected investment or project [11]. The application of NPV in capital budgeting and investments is widely presented in the literature, e.g., [7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The researchers emphasise the importance of NPV for investment planning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers emphasise the importance of NPV for investment planning. Net Present Value enables the comparison between the money that must be paid to complete the planned investment with all the cash flows that the undertaking will generate in the future [7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The building sector is the most energy-consuming sector globally, as it consumes 35% of the total power generated and emits CO 2 at everhigher levels, i.e.,~10 GT which is equivalent to one-third of the total emissions of the world. This means that the building sector is moving away from the Paris Agreement of maintaining the global mean temperature rise below 2 • C. One of the main reasons behind such alarming environmental threats is that fossil fuels are the main source of energy generation which cause pollution and global warming [2] and the conventional means of thermal regulation of building such as heaters, air conditioners and HVAC systems are contributing in the greenhouse effects [3]. Renewable energy, e.g., solar, wind, biomass and geothermal, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Across the world, the energy requirement is increasing rapidly due to the attraction of urbanization facilities and the human population [6][7][8]. The world's largest CO 2 contributors are buildings, as the current building structures are demolished and rebuilt as huge buildings like skyscrapers to accommodate the population in urban areas [9][10][11]. It is reported that the building sector is responsible for almost 40% of global CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%